Tinjauan Sistem Penyimpanan Dengan Lama Waktu Pengambilan Berkas Rekam Medis Di Rumah Sakit Ibu Dan Anak Artha Mahinrus Medan2021 - Puput Melati Hutauruk; Yeyi Gusla Nengsih; Ellan Eltitah Riya Zebua (Akademi Perekam dan Informasi Kesehatan Imelda, 2023)
Storage (Filling) is an activity of storing, structuring, or storing medical record files facilitate retrieval. The aim of this research is to determine the overview of the storage system with the length of time for retrieval of medical record files at RSIA Artha Mahinrus Medan. This research is descriptive qualitative to see by describing the results as they are and comparing them with the theory which is then drawn conclusions. The time of the study was carried out in May at the Artha Mahinrus Mother and Child Hospital, Medan. The population and sample used are medical record employees in the registration and storage division (filling). The instruments used in data collection were observation and interviews. Based on the results of this study, it shows that the storage system at the Artha Mahinrus Mother and Child Hospital Medan is a centralized storage system, by combining medical record files in one room. The time of taking medical record files is very influential on education, age, years of service and storage shelves. The education of medical record file storage officers is not all D3 medical record graduates. But the storage process continues to run well. for the medical record retrieval process, it is hoped that the retrieval process from registration to the polyclinic is expected to be improved again with a time of 10 minutes.